Exploring social capital influencing entrepreneurial process among immigrant entrepreneurs in Malaysia - Zizah Che Senik,; Nurul Atasha Jamaludin,; Rosmah Mat Isa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Immigrant entrepreneurship has been widely discussed in various perspectives. Yet, their entrepreneurial process has received less attention from the aspect of social capital. This paper intends to explore the role of social capital dimensions (structural, relational, and cognitive) in the entrepreneurial process (discovery and exploitation of opportunity). In-depth interview approach was conducted with six Thai immigrant restaurant-preneurs (TIRps) in Malaysia. The findings revealed that the structural social capital is the most important dimension for TIRps highlighting the supports from family and friends which transpired at both stages of the entrepreneurial process. The study that is based on social capital and entrepreneurial process perspectives also demonstrated the significance of local consumers’ eating-out habits identified as structural social capital and local preferences for Thai cuisines identified as cognitive social capital. This signifies the emergence of the Consumer Culture Theory in research on immigrant entrepreneurship. This study contributes to an integrated model of immigrant entrepreneurship and a set of propositions. For practicality, the findings provide some guidelines for policymakers to develop training programmes by leveraging on social capital for further development of Malaysian entrepreneurs.